Grammatical Analysis of African American Vernacular English in The Eminem Show Album: A Linguistics Perspective - Ichwan Suyudi; Agung Prasetyo Wibowo; Luthfi Chanafiah Pasha (Langkawi: Journal of The Association for Arabic and English, 2023)
Albeit the research on African American Vernacular English (AAVE) as nonstandard form of English spoken by African Americans in lower socioeconomic classes has been documented by many scholars, little is known about it from the perspective of Wolfram's theory. To fill this lacuna, the present study aims to elucidate the grammatical elements of Eminem's lyrics song in the album "The Eminem Show." This single case study showcased 32 lyrics song from Eminem's album with that seven grammatical features such as copula/auxiliary absence, the invariant be, the remote been, the subject verb agreement, the negation, the question formation, and the nominals. The findings found that negation is the most common grammatical features whereas the invariant be is the least common. The findings indicated that songs serve as a platform for asserting identity and criticizing diverse social, cultural, political, and economic issues. The performers are free to improvise in accordance with the tendencies and interests of the critic. Thus, the song can serve both to identify the current social crisis and as a catalyst for the crisis itself.